Enhancing production and income through technological interventions under changing climatic scenario - Joshi, Kushagra; Kandpal, Ankita; Panday, S C; Stanley, J; Meena, Vijay Singh; Pattanayak, Arunava (Indian Farming, 2021)
This article describes the importance of the National Mission for Sustaining Himalayan Ecosystem (NMSHE) project in the Indian Himalayan region under changing climatic scenario.